Investigating the effect of bouncing type on the physiological demands of trampolining. Issue 1 (2nd January 2021) - Clement, Tane; Alexander, Keith; Draper, Nick
Abstract: Purpose: The aim of this study was to investigate whether altering the bounce style affects the physiological demands of trampolining. Methods: Twenty-eight healthy adults completed five, three-minute exercise bouts on a trampoline where; heart rate (HR), V ˙ O 2 (mL/min) and rate of EE (kJ/min) were collected for five different bouncing variations. Results: A one-way repeated measures MANOVA was then used to assess whether significant differences existed between the different bounce types for HR V ˙ O 2 and EE. A significant difference was found ( F 12, 280  = 20.886, p  = 0.0005), so a series of one-way repeated measures ANOVAs were used to identify the degree of significance. For V ˙ O 2 ( F 2.421, 27  = 64.079, p  = 0.0005, ηp 2  = 0.7) and EE ( F 2.989, 27  = 44.979, p  = 0.0005, ηp 2  = 0.6). Post-hoc tests found that for both V ˙ O 2 and EE a significant difference existed between the conventional bounce and each of the bounce variates ( p  = 0.0005). Conclusion: The results from this study indicated altering the bounce style does have a significant effect on the physiological demands of trampolining. The energy expenditure (EE) equation for trampolining can now be updated to more accurately reflect the rate of EE while performing different bounce styles.